PERAN GLOBALISASI TERHADAP KEBUDAYAAN LOKAL DI INDONESIA - Nur Areefa; Sobirin (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
Globalization has significantly impacted local cultures in Indonesia, affecting various aspects such as cultural consumption patterns, social values, forms of art and tradition, the impact of information technology, as well as the economy and cultural industries. This article explores how globalization influences the cultural identity of individuals and communities, and what resistance and adaptation strategies are used to maintain cultural diversity amidst the current global homogenization. This literature study shows that changes in cultural consumption behavior, particularly among the younger generation, indicate the adoption and adaptation of global culture to the local context. Societal values also experience shifts, with traditional values overlapping with global values. Changes in arts and traditions reflect the creative adaptation of local artists and craftsmen to global tastes. Information technology, especially the internet and social media, plays a crucial role in the dissemination and preservation of local culture. The local cultural industry, including the tourism and craft industry, faces challenges and opportunities in the global market context. Facing the threat of cultural homogenization, many local communities actively strive to maintain their cultural identity through education, cultural festivals, and the use of technology. Resisting homogenization and adapting global elements without losing local identity are the two main approaches to preserving cultural diversity. Overall, globalization brings both challenges and opportunities for local cultures in Indonesia. Through effective resilience and adaptation strategies, the Indonesian society can preserve their cultural heritage while remaining relevant in a global context. Ensuring that cultural diversity continues to endure, thrive, and contribute valuable insights to the world's cultural heritage requires joint efforts from individuals, communities, and the government. Keywords: Globalization, Local Culture, Indonesia